The legal regulation of the distribution of parliamentary seats in Iraq under the law (45) for the year 2013 amended and its effects on the value of the parliamentary seat - Abdullah, Ahmed; Adil, Musadak (Journal of Legal Sciences, 2022)
The search came under the title "The Legal division of the distribution of seats in Iraq under Law No. (45) for the year 2013 and its effects on the value of the seat of Parliament)" as part of the response to the requirements of the current circumstances that are going through Iraq, after the experience of each of the electoral experiments that we are waging every four Nawat to elect a new house of representatives that cries out for amending the distribution systems of parliamentary seats, so that some have imagined that the devil is behind all the darkness of the crises in society, and that it is inevitable to believe that the distribution systems of the parliamentary seats is a legal ploy to confiscate the will of the people. The research is from two sections, the first took up the first parliamentary elections held under Law No. (45) for the year 2013 and was in 2014, she indicated the legal regulation of the allocation of seats in the parliament, how to determine the winners of these seats and how to distribute seats on them and the implications of the value of the seat b In terms of the wastage of votes and the equal value of the parliamentary seat in the provinces – electoral districts – and equal value between the electoral lists, while the second addressed the same demands in the elections of the House of Representatives in 2018, and then the conclusion included conclusions and a set of recommendations.